Effect of Passive Leg Raising on Blood Pressure in Post-Spinal Anesthesia Caesarean Section Patients: A Study at PKU Muhammadiyah Bantul Hospital - Rasidin, Muhammad Sobari; Rosidah, Istiqomah; Azizah, Aisyah Nur (Fakultas Kesehatan, Universitas Nurul Jadid, 2025)
Introduction: Sectio Caesarea mostly uses spinal anesthesia and is most commonly used. The effect of spinal anesthesia is hypotension. In a study of sectio caesarea more than 40% experienced hypotension. Passive Leg Raising (PLR) can be an alternative for the incidence of hypotension in sectio caesarea spinal anesthesia patients.Objectives: This study aims to determine the effect of passive leg raising on the increase in blood pressure of post spinal anesthesia sectio caesarea patients in the intervention and control groups at PKU Muhammadiyah Bantul Hospital. Methods: This type of research is quantitative experiment with quassy experimental design pre-test post-test with control group. The sampling technique used simple random sampling technique with a total of 30 respondents. Results: The results of the Wilcoxon test on systolic blood pressure with a p-value in the intervention group of 0.001 <0.05 and the control group of 0.007 <0.05, while in diastolic blood pressure, the p-value of the intervention group was 0.001 <0.05 and the control group was 0.001 <0.05. In the results of the mann-whitney test, the p-value on systolic blood pressure was 0.008<0.05 and diastolic blood pressure was 0.005<0.05. Conclusions: There is a significant effect between Passive Leg Raising (PLR) on blood pressure of post spinal anesthesia sectio caesarea patients at PKU Muhammadiyah Bantul Hospital.Introduction: Sectio Caesarea mostly uses spinal anesthesia and is most commonly used. The effect of spinal anesthesia is hypotension. In a study of sectio caesarea more than 40% experienced hypotension. Passive Leg Raising (PLR) can be an alternative for the incidence of hypotension in sectio caesarea spinal anesthesia patients. Objectives: This study aims to determine the effect of passive leg raising on the increase in blood pressure of post spinal anesthesia sectio caesarea patients in the intervention and control groups at PKU Muhammadiyah Bantul Hospital. Methods: This type of research is quantitative experiment with quassy experimental design pre-test post-test with control group. The sampling technique used simple random sampling technique with a total of 30 respondents. Results: The results of the Wilcoxon test on systolic blood pressure with a p-value in the intervention group of 0.001 <0.05 and the control group of 0.007 <0.05, while in diastolic blood pressure, the p-value of the intervention group was 0.001 <0.05 and the control group was 0.001 <0.05. In the results of the mann-whitney test, the p-value on systolic blood pressure was 0.008<0.05 and diastolic blood pressure was 0.005<0.05. Conclusions: There is a significant effect between Passive Leg Raising (PLR) on blood pressure of post spinal anesthesia sectio caesarea patients at PKU Muhammadiyah Bantul Hospital.